(untitled) (Italiano LinguaDue, 2023)
This article identifies and analyses a catalogue of English loanwords from Italian merchant texts; specifically commercial letters (1392-1401) sent to employees in the service of the ‘merchant of Prato’, Francesco Datini, and his company. Research on loanwords in late medieval London has already shown a significant degree of linguistic exchange between Italy and England. The corpus studied here consists of seventy-eight letters published by Nicolini (2020) which are subjected to a linguistic analysis for the first time in the paper. Within the corpus, twenty-five English loanwords were identified, revealing a far greater degree of lexical exchange than what has previously been recorded in the literature. However, there were occurrences of loanword transfer where the etyma or direction of transfer was unclear and therefore not easily identifiable. Italian morphological changes of English loanwords include but are not limited to: adjectival and noun case marking, gemination, deletion of double consonants, apocope, and phonological reduction. The results provide insight into the extent of language and cultural exchange between local English speakers and Italian merchant immigrants in the period immediately preceding the Renaissance. Sul trasferimento di prestiti e fenomeni di scambio linguistico dall’inglese all’italiano, 1392-1401 In questo articolo si identifica e analizza un catalogo di prestiti inglesi da testi commerciali italiani; in particolare, lettere commerciali (1392-1401) inviate ai lavoratori al servizio del “mercante di Prato”, Francesco Datini, e alla sua società. Gli studi sui prestiti nella Londra del tardo medioevo hanno già mostrato una presenza significativa di scambi linguistici tra l’Italia e l’Inghilterra. Il corpus qui analizzato consiste di 78 lettere pubblicate da Nicolini (2020) e che, per la prima volta, in questo studio, sono oggetto di analisi linguistica. Nel corpus, sono stati individuati 25 prestiti inglesi che testimoniano un livello di scambio lessicale superiore a quanto registrato dalla precedente letteratura. Tuttavia, ci sono casi in cui l’etimo o la direzione dello scambio è dubbia e di conseguenza non facilmente identificabile. I cambiamenti morfologici dell’italiano applicati ai prestiti inglesi includono, tra i vari, anche i seguenti: la flessione aggettivale e nominale, il raddoppiamento, lo scempiamento delle consonanti doppie, l’apocope e la riduzione fonologica. I risultati offrono una prospettiva sulle proporzioni degli scambi linguistici e culturali tra nativi inglesi e mercanti italiani immigrati nel periodo immediatamente precedente il Rinascimento.